2021
DOI: 10.1186/s12889-021-11187-9
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability and feasibility of strategies to shield the vulnerable during the COVID-19 outbreak: a qualitative study in six Sudanese communities

Abstract: Background Shielding of high-risk groups from coronavirus disease (COVID-19) has been suggested as a realistic alternative to severe movement restrictions during the COVID-19 epidemic in low-income countries. The intervention entails the establishment of ‘green zones’ for high-risk persons to live in, either within their homes or in communal structures, in a safe and dignified manner, for extended periods of time during the epidemic. To our knowledge, this concept has not been tested or evaluat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…We investigated COVID-19 knowledge, risk perception and precautionary behaviours during the epidemic's early phase in six Sudan communities. This analysis complements ndings reported in our earlier paper describing the acceptability and feasibility of shielding high-risk groups to prevent COVID-19 transmission [12]. Here, we speci cally report beliefs about COVID-19 and how and why households with members at higher risk of severe COVID-19 outcomes understand COVID-19 and the perception of risk to themselves and their family members.…”
supporting
confidence: 76%
See 1 more Smart Citation
“…We investigated COVID-19 knowledge, risk perception and precautionary behaviours during the epidemic's early phase in six Sudan communities. This analysis complements ndings reported in our earlier paper describing the acceptability and feasibility of shielding high-risk groups to prevent COVID-19 transmission [12]. Here, we speci cally report beliefs about COVID-19 and how and why households with members at higher risk of severe COVID-19 outcomes understand COVID-19 and the perception of risk to themselves and their family members.…”
supporting
confidence: 76%
“…The communities chosen for our study ranged from urban and peri-urban settings to rural and camp settings, and included Umbadda district and Tuti Island in Khartoum State, El-Obeid and Damazin North in North Kordofan State, Aldanagla village in the south of Gezira State, and Dereij camp for internally displaced persons (IDP) in South Darfur). Further details on study setting have been mentioned elsewhere [12].…”
Section: Study Design and Settingmentioning
confidence: 99%
“…This is especially important when using IATS for qualitative research, which tends to involve lengthy interviews. In some of the 15 qualitative studies identified in this scoping review, the average or median length of each session was prone to be long (over 40 minutes) [31][32][33][34][35].…”
Section: Summary Of Evidencementioning
confidence: 99%
“…Nevertheless, to guide interested readers as well as to pool literature related to pneumonia among Sudanese population and for further research prospect, all related articles according to the current search strategy are depicted in (Table 2). Abd El-Raheem et al [28] Characteristics and severity of COVID-19 among Sudanese patients during the waves of the pandemic Abdelmagid et al [29] Acceptability and feasibility of strategies to shield the vulnerable during the COVID-19 outbreak: a qualitative study in six Sudanese communities Abdou et al [30] The coronavirus disease 2019 (COVID-19) vaccination psychological antecedent assessment using the Arabic 5c validated tool: An online survey in 13 Arab countries Abouzid et al [31] Influence of COVID-19 on lifestyle behaviors in the Middle East and North Africa Region: a survey of 5896 individuals Ahmed et al [32] Impact of the COVID-19 pandemic on intimate partner violence in Sudan, Malawi and Kenya Ahmed et al [33] COVID-19 in Sudan Ahmed et al [34] Clinical characteristics, complications, and predictors of outcome of hospitalized adult Sudanese patients with COVID-19 and malaria coinfection in Sudan: A multicenter retrospective cross-sectional study Ahmed et al [35] Controlling the spread of COVID-19 in Sudan with limited resources: a unique community-engaged approach Ali et al [36] The role of integrated programs in the prevention of COVID-19 in a humanitarian setting Aljak et al [37] The first laboratory-confirmed imported infections of SARS-CoV-2 in Sudan Attaallah et al [38] The Prognostic Value of Thrombocytopenia in COVID-19 Pneumonia, Gezira Isolation Centers, Sudan Aung et al [39] Community responses to COVID-19 pandemic first wave containment measures: a multinational study Bara'a et al [40] Coronavirus 2019-like illness and public adherence to preventive measures, Sudan 2020 Deek et al [41] A multi-centric study on validation of the Fear Scale for COVID-19 in five Arabic speaking countries Elagib et al [42] Knowledge, attitude, and practice regarding infection control measures among dental students during COVID-19 pandemic Elhadi et al [43] The formidable task of fighting COVID-19 in Sudan El-Sadig et al [44] Obstacles faced by healthcare providers during COVID-19 pandemic in Sudan El-Sadig et al [45] Impact of COVID-19 on doctors and healthcare providers during the pandemic in Sudan Fahal et al [46] The Mycetoma Research Centre experience during the COVID-19 pandemic: obstacles and beyond Gayawan et al [47] The spatio-temporal pandemic dynamics of COVI...…”
Section: Covid 19 Studiesmentioning
confidence: 99%